A universal strategy for the one-pot synthesis of SERS tags. Issue 17 (24th April 2018) - Li, Jin; Liu, Huiqiao; Rong, Pengfei; Zhou, Wen; Gao, Xiaohu; Liu, Dingbin
Abstract : We report a simple, rapid, and robust methodology for the one-pot preparation of SERS tags. Abstract : Surface-enhanced Raman scattering (SERS) tags have attracted tremendous attention in diverse fields owing to their outstanding sensitivity and multiplexing capability. However, the selection of Raman dyes that can be immobilized onto metal nanoparticles is very limited, because certain chemical groups are needed in the dye molecules to interact either with the metal surface or through some intermediate layers. Here, we report a simple, rapid, and robust platform methodology for the one-pot preparation of Raman nanoprobes without the constraints of Raman dye chemical structures. We demonstrate this general approach by immobilizing dye molecules on silver nanoparticle surfaces that were difficult to incorporate previously, and show their applications in multiplexed immunohistochemistry (IHC). We expect that this platform nanotechnology will significantly expand the library of SERS tags and their biomedical uses.